Bread waste – a potential feedstock for sustainable circular biorefineries - Kumar, Vinod; Brancoli, Pedro; Narisetty, Vivek; Wallace, Stephen; Charalampopoulos, Dimitris; Kumar Dubey, Brajesh; Kumar, Gopalakrishnan; Bhatnagar, Amit; Bhatia, Shashi Kant; Taherzadeh, Mohammad J. (Elsevier, 2023)
The management of staggering volume of food waste generated (∼1.3 billion tons) is a serious challenge. The readily available untapped food waste can be promising feedstock for setting up biorefineries and one good example is bread waste (BW). The current review emphasis on capability of BW as feedstock for sustainable production of platform and commercially important chemicals. It describes the availability of BW (>100 million tons) to serve as a feedstock for sustainable biorefineries followed by examples of platform chemicals which have been produced using BW including ethanol, lactic acid, succinic acid and 2,3-butanediol through biological route. The BW-based production of these metabolites is compared against 1G and 2G (lignocellulosic biomass) feedstocks. The review also discusses logistic and supply chain challenges associated with use of BW as feedstock. Towards the end, it is concluded with a discussion on life cycle analysis of BW-based production and comparison with other feedstocks.
Keywords: Bread waste; Logistics and supply chain; Life cycle assessment; Organic acids; Alcohols and Diols